An assessment model based on the role of knowledge management factors in project management performance of business organisations in the UAE - Abdulrahman Alhammadi, Eman Mohammed (2022)
Knowledge management has emerged over the last few decades and became one of the most debated and discussed management concepts. However, in the project management industry, knowledge management (KM) investigation in the eastern countries, especially in the middle east, is still a way behind western countries in this area investigation. Hence, business organisations from the UAE have a tendency for poor performance compared to the Western and Southern business organisations, and failed to facilitate organisational efficiency by ignoring the importance of managing knowledge appropriately. Additionally, the impact of knowledge management on project management success has not been researched enough by using both the infrastructure and process capabilities of the business organisations in the United Arab Emirates (UAE). This research intends to fill this gap in KM investigation by examining the impact of knowledge management factors on construction project management successes of business organisations in the United Arab Emirates (UAE). This study adopted a quantitative method design and simple random sampling was applied to pick a representative sample of 271 respondents. The respondents consist of managers and employees from various business organisations around the UAE. The questionnaire survey was the chosen instrument that was employed in this study and after which, the data collected was analysed using descriptive statistics and multiple regressions. Structural Equation Modelling (SEM) technique was used for confirmatory factor analysis, followed by the specification and estimation of the models. The results found that there are four factors of KM that have a significant impact on construction project management, including knowledge process, knowledge leadership, knowledge technology, and knowledge culture. The findings also showed that these factors of KM have a significant relationship with project management success in construction organizations in the UAE. It is concluded that it is important to improve KM since it is essential to enhance construction project management performance, which in turn leads to improving the organization business performance.